Shared medical appointments and quality of life for children with HIV-AIDS - Perdani, Roro Rukmi Windi; Farishal, Ahmad; Wardani, Amanda Saphira (Indonesian Pediatric Society, 2024)
Background The human immunodeficiency virus (HIV) infects immune cells and weakens the immune system. There are 36.9 million HIV sufferers worldwide, with 1.8 million of them being children. Children with HIV and their parents may benefit from focus group discussions, also known as shared medical appointments (SMAs). SMAs represent an educational method capable of enhancing the quality of healthcare services. However, this method remains relatively under-researched in HIV/AIDS patients. Objective To assess the impact of SMA on the quality of life of children with HIV-AIDS. Methods This quasi-experimental study with a cross-sectional approach was carried out for 2 months. Subjects participated in SMAs, accompanied by a pediatrician as facilitator. Subjects filled three Pediatric Quality of Life (PedsQL) questionnaires (Inventory 4.0, General Well-Being Scale 3.0, and Healthcare Satisfaction 3.0), before and after attending SMAs. We compared the results. Results There were 12 respondents, with the majority aged 5-10 years (50%), and a higher proportion of male than female (33.3%). The majority of boys had stage 3 HIV, while most girls had stage 2 HIV. According to the PedsQL Inventory module, the average quality of life for the physical aspect was the highest (83), while the lowest was observed in the school aspect (45). In the General Well-being module, the average emotional health scores were 84 before and 93 after SMAs, which were higher than the overall health scores (68 and 77 before and after SMAs, respectively). In the Healthcare Satisfaction module, the lowest average scores were in family satisfaction (52 before and 64 after SMAs), whereas the highest were in satisfaction with healthcare provider treatment (87 and 81 before and after SMAs, respectively). There was a significant increase before and after the SMAs in emotional health (P=0.009). Conclusion An improvement in emotional health was observed based on the General Well-being module of the PedsQL before and after SMAs intervention. Thus, SMAs may potentially improve the quality of life for children with HIV-AIDS.